Association of hyperemesis gravidarum with the risk of development of small for gestational age fetus - Ostafiichuk, S.O.; Volosovskiy , P.R.; Prudnikov , P.M.; Henyk , N.I.; Makarchuk , O.M. (Medicni Perspektivi, 2022)
The goal of this study was to determine the association of hyperemesis gravidarum with the risk of development small for of fetus gestational age (SGA). Materials and methods. There were studied 327 pregnant women. The main group included 218 women with hyperemesis gravidarum, who were divided into two groups: 140 patients who were first hospitalized with hyperemesis gravidarum in the first trimester (up to 12 weeks of pregnancy) and 78 - who were first hospitalized with hyperemesis gravidarum in the second trimester (12-21 weeks of pregnancy). 109 pregnant women without vomiting were at control group. The diagnosis of SGA fetus was established on the basis of standard ultrasonic fetometry on the ALOKA SSD-1700. Determination of human serum chorionic gonadotropin (HCG) levels was performed at 15-20 weeks and was evaluated as MoM. The results were statistically analyzed using Statistica 10 (Serial Number: STA999K347150-W) and MEDCALC®. Results. In the main group, the SGA fetus was 3.4-fold more frequent compared with pregnant women in the control group (9.6% vs. 2.8%, p<0.05; OR=3.77; 95%CI:1,10-12.92). It was found that hyperemesis gravidarum in the first trimester does not affect the deviation of fetal weight deviations (p>0.05). However, hyperemesis gravidarum in pregnant women in the second trimester increases the risk of developing SGA fetus (OR=6.42; 95%CI 1.75-23.62; p<0.01) compared with control. Pregnant women with HCG≥2.5 MoM were 3.0-fold more likely to be diagnosed SGA fetus than with HCG<2.5 MoM (75.0% vs. 25.0%, p<0.001; OR=9.00; 95%CI:1.42-57.12) and 2.3-fold compared with the development of the normal fetus (75.0% vs. 33.3%, p<0.001; OR=6.00; 95%CI:1.47-24,4). Conclusion. Hyperemesis gravidarum in the second trimester of pregnancy and elevation of HCG level in the second trimester (≥2,5 МоМ) can be seen as markers of placental disfunction and high risk for SGA fetus.